2013
DOI: 10.1002/stem.1324
|View full text |Cite
|
Sign up to set email alerts
|

Functional Involvements of Heterogeneous Nuclear Ribonucleoprotein A1 in Smooth Muscle Differentiation from Stem Cells In Vitro and In Vivo

Abstract: To investigate the functional involvements of heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) in smooth muscle cell (SMC) differentiation from stem cells, embryonic stem cells were cultivated on collagen IV-coated plates to allow for SMC differentiation. We found that hnRNPA1 gene and protein expression was upregulated significantly during differentiation and coexpressed with SMC differentiation markers in the stem cell-derived SMCs as well as embryonic SMCs of 12.5 days of mouse embryos. hnRNPA1 knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Data shown in Figure 7a revealed that gene expression levels of all three factors were significantly upregulated by SirT1, suggesting SirT1 may have a direct role in regulation of these transcription factors during SMC differentiation. Indeed, luciferase activity assays with SRF, MEF2c and Myocd gene reporters 11 showed that the SirT1 overexpression significantly increased SRF, MEF2c or Myocd gene-promoter activities (Figure 7b), indicating that SirT1 upregulates transcriptional activity of these three genes. Importantly, data SirT1 promotes SMC gene expression through inhibiting H3K9 methylation around SMC gene promoters.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Data shown in Figure 7a revealed that gene expression levels of all three factors were significantly upregulated by SirT1, suggesting SirT1 may have a direct role in regulation of these transcription factors during SMC differentiation. Indeed, luciferase activity assays with SRF, MEF2c and Myocd gene reporters 11 showed that the SirT1 overexpression significantly increased SRF, MEF2c or Myocd gene-promoter activities (Figure 7b), indicating that SirT1 upregulates transcriptional activity of these three genes. Importantly, data SirT1 promotes SMC gene expression through inhibiting H3K9 methylation around SMC gene promoters.…”
Section: Resultsmentioning
confidence: 96%
“…Murine ESCs were induced to differentiate towards SMCs as described previously (Supplementary Figure S1). [11][12][13][14] miRNA microarrays analysis was conducted to identify potential miRNA candidates for SMC differentiation, and the data revealed that miR-290 family members, the reported ESC-specific miRNA cluster, 15 were dramatically downregulated upon differentiation (Supplementary Table S1). Conversely, muscle differentiation-related miRNAs (miR-143/145/133) were increased in our SMC differentiation model, while SMC proliferation-related miR-21 was undetectable at early stage but dramatically increased at late stage of SMC differentiation, indicating that some miRNAs may initiate SMC differentiation, whereas others may have important roles in the late stage of SMC differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations